"My Research Is Their Business, but I'm Not Their Business": Patient and Clinician Perspectives on Commercialization of Precision Oncology Data. (13th March 2020) - Spector‐Bagdady, Kayte; Krenz, Chris D.; Brummel, Collin; Brenner, J. Chad; Bradford, Carol R.; Shuman, Andrew G.
Abstract: Background: Genetic sequencing and precision oncology have supported clinical breakthroughs but depend upon access to vast arrays of research specimens and data. One way for academic medical centers to fund such infrastructure and research is "commercialization" of access to specimens and data to industry. Here we explore patient and clinician perspectives regarding cancer specimen and data commercialization with the goal of improving such processes in the future. Materials and Methods: This qualitative analysis was embedded within a prospective precision oncology sequencing study of adults with head and neck cancer. Via semistructured dyadic interviews with patients with cancer and their doctors, we assessed understanding and concerns regarding potential commercialization, opinions regarding investment of profits, and perspectives regarding the return of information directly to participants from industry. Results: Several patient‐ and clinician‐participants did not understand that the consent form already permitted commercialization of patient genetic data and expressed concerns regarding who would profit from the data, how profits would be used, and privacy and access. Patients were generally more comfortable with commercialization than clinicians. Many patients and clinicians were comfortable with investing profits back into research, but clinicians were more interested in investment in head and neck cancer research specifically. Patients generally supported potential return‐of‐results from a private entity, but their clinicians were more skeptical. Conclusion: Our results illustrate the limitations of mandatory disclosures in the informed consent process. The voices of both patients and their doctors are critical to mitigate violations of privacy and a degradation of trust as stakeholders negotiate the terms of academic and commercial engagement. Implications for Practice: Further education is needed regarding how and why specimens and data in precision oncology research may be commercialized for both patients and providers alike. This process will require increased transparency, comprehension, and engagement of involved stakeholders. Abstract : To better understand perspectives on cancer specimen and data commercialization, interviews of patients participating in a prospective precision medicine cancer sequencing study were conducted, along with corresponding interviews with the patients' referring doctors. This article reports the results and aims to improve the consent process for biospecimen and health data sharing and commercialization.